DIPLOMA JOB PROCESSING ON PAINTING ON AN ARTISTICALLY-GRAPHIC FACULTY (Pedagogy of Higher and Secondary Education, 2022)
Questions, which must help the students of 3 - 4 courses to be determined in the choice of theme of diploma on painting, are examined in the article, the sequence of diploma job processing and structure of diploma message is examined.